Question tags across New Englishes. Issue 4 (14th March 2021) - Westphal, Michael
Abstract: This paper presents a cross‐variety analysis of (variant and invariant) question tags in Philippine and Trinidadian English, using six dialogic text types from the corresponding components of the International Corpus of English (ICE). The cross‐variety comparison considers the similarities and differences across the two New Englishes in terms of question tag forms and functions and the constraints of variation, particularly the effect of text type. This analysis demonstrates that there are mainly differences in terms of forms, however, several similarities predominate: Filipino and Trinidadian speakers have the same communicative needs in specific situations and use question tags in similar ways, often selecting the same forms for the same functions. In‐depth analyses of question tags – and discourse markers in general – offer new possibilities for corpus‐based research on world Englishes, as established tools like ICE can be used in innovative ways.